3D recycled mortar printing: System development, process design, material properties and on-site printing. (November 2020) - Xiao, Jianzhuang; Zou, Shuai; Yu, Ying; Wang, Yu; Ding, Tao; Zhu, Ying; Yu, Jiangtao; Li, Shuaishuai; Duan, Zhenhua; Wu, Yuching; Li, Lingzhi
Abstract: 3D concrete printing (3DCP) has received worldwide attention in recent years. However, very limited studies have been carried out on the simultaneous research and mutual coordination of printing system, process design and printing material. In this study, a printing system including supporting subsystem, controlling subsystem, feeding subsystem, and extruding subsystem was developed by considering the properties of mortar and the large-size characteristics of 3D mortar printing (3DMP). The process design of 3DMP, such as tool path and printing parameters, was also redesigned to improve the printing qualities. The properties of printing mortars with/without recycled sand were then comparatively studied, followed by a successful on-site printing of a 2.5 m × 2.5 m × 3 m room. Results have shown that replacing natural sand with 25% of recycled sand caused higher green strength and no obvious decrease in hardened mechanical properties. By properly adjusting printing parameters, the printing mortars (with or without recycled sand) can be well-matched with the printing system. This verifies the practicability of the developed printing system as well as the method of partial application of recycled sand in 3DMP. Besides, it is recommended that both real-time monitoring system and continuous printing are necessary to achieve higher printing quality and efficiency. Highlights: Hardware and software are developed for 3D recycled mortar printing. The printing process is redesigned to improve printing qualities. Fresh and hardened properties of printing materials with recycled sand are tested. Feasibility of the developed system is verified by a 3D printed building room.